Investigação experimental da formação do cavaco na usinagem do aço ABNT 1045 e do ferro fundido nodular - Silva, Márcio Aurélio da (2008)
The chip formation is influenced by several cut parameters which also affect the forces, tensions, powers and temperatures generated during the machining process. Although they have been studied for more than 100 years, still today, the involved mechanisms of deformation are not totally know, due to the fact that the chip formation involves high temperatures and high levels of deformation. This research aims at studying the basic process of chip formation, as well as the influence of the main cut parameters such as cutting speed, feed rate, cutting fluid, tool coating and machined material, besides determining the force of residual cut for ABNT 1045 steel. The inquiry was based on the classification of the chips concerning their type and form, thicknesses values, shear angles, stresses degree and in the monitoring of the cutting forces. Micrographs and measurement of the chips microhardness were made in order to achieve a detailed structural analysis. The results found have shown that the parameters and analyzed conditions really influenced the formation of the chips, being the feed rate more significant than the cutting speed. The tool coating and the cutting fluid had a great influence on the chip formation as well as on the cutting forces during the machining of ABNT 1045 steel and nodular casting iron. The residual cutting force for the ABNT 1045 steel varied between 45 N and 52N.